Synthesis and characterization of MOF polymer nanocomposites for Chromium adsorption and their antimicrobial properties - Amaravathi Chinthamreddy; Suresh Koppula; Sujith Benerjee Nallamalla; Geetha Karra; Surendra Babu Manabolu Surya (Chemical Physics Impact, 2024)
This study describes the preparation of MOF and its polymer composites, namely Co@BTC(MOF1), Co@BTC(PAA)(MOF2), and Co@BTC(PAA)(CTAB)(MOF3), by assimilating cobalt nitrate hexahydrate [(CoNO3)2·6H2O] with trimesic acid, polyacrylic acid (PAA), and cetyltrimethylammonium bromide (CTAB) using a solvothermal procedure at 100℃ for 12 h. All MOF composites exhibited remarkable adsorption properties and thermal and chemical stability properties. These polymer composite MOFs are explored for the adsorption of anionic dyes such as Methyl Orange (MO) and Congo Red (CR), cationic dye Methylene Blue (MB), and Chromium (VI) from wastewater. A 90–95 % adsorption rate for MO and CR dyes was observed within 60 min using 100 mg of MOF composites. Within 60 min, the MOF composites achieved an adsorption rate of 90–95 % for MO and CR dyes when 100 mg of the composites were used. Furthermore, MOF2 and MOF3 have exhibited a remarkable 92 % efficiency in adsorbing Cr(VI) during one hour, following a pseudo-second-order kinetic model. The composites were examined for their anti-bacterial efficacy against Bacillus (Gram-positive), E. Coli (Gram-negative), and Saccharomyces cerevisiae. The results were compared to ciprofloxacin, a conventional antibiotic, using the agar diffusion method. MOF2 and MOF3 have demonstrated long-lasting and potent antimicrobial activity, successfully inhibiting the growth of bacteria for a period of at least 90 days. Furthermore, the polymer composites of MOFs exhibit notable capability in scavenging radicals, particularly against ascorbic acid, as determined by the DPPH method. The inhibition rates for the composites are 68.7 % and 65.9 %, respectively. This indicates that these polymer MOF composites possess potent anti-microbial activity, making them an ideal candidate for addressing the inhibition of bacterial growth.